Managing the new enterprise the proof, not the hype - Kern, Harris (SunSoft Press, 1996)
For CEOs, CIOs, VPs of IT, and all levels of IT management and technical staff. Based on the authors' real-life experiences implementing client-server production environments over the past six years, this book gives the "how to" information needed to implement a heterogeneous client-server infrastructure, and deals with the "people issues" of getting everyone to work together.